Implementasi Konsep Edutaintment Dalam Pembelajaran Anak Usia Dini: Edutainment - Alfain Azhary; Ella Dwi Febrianti; M. Bilqis Ainul Mardiyah; Ahmad Mujadid Alfaini (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
Early childhood education has an important role in training and developing intelligence and other aspects of each individual. The edutainment concept offers an interesting approach to early childhood education. Edutainment learning can combine the concept of play, media, and active learning processes, such as the use of play methods in learning science and nature. The STEAM learning model is a learning approach that links science, technology, engineering, art, and mathematics. STEAM learning aims to increase children's interest, creativity, critical thinking, and communication in an interesting and fun way. The method used in this study uses a descriptive qualitative approach. Data collection techniques were carried out by observation and interviews about the learning process carried out by TK IT Alam Nurul Islam Yogyakarta teachers, then the results of research supported by documentation. The data analysis technique used is a qualitative analysis technique, data obtained from various sources, using triangulation techniques. In conclusion, the implementation of the concept of edutainment in early childhood learning can improve the quality of early childhood education. Edutainment learning creates a pleasant atmosphere, encourages children's independence and confidence, and combines the concept of play with formal learning. STEAM model learning can also be a natural learning tool every day through play and exploration activities.